risks Mass Wasting in the Dohuk basin - Hussain, Zainb Ibraheem (Al-Adab Journal, 2020)
The Dohuk Basin located in the northern part of Iraq was studied within the range of high folds. The study examined the most important geomorphological factors and processes that contribute to the movement of ground materials over slopes and classification of their types by relying on field study and the use of geographic information systems technology The research concluded that the geomorphological factors and processes represented by the geological formation, the slope, the direction of the slope, the elevation from the sea level and the Gulley erosion processes have the great effect on the occurrence of movement of ground materials in the basin slopes as well as human interventions. The average severity of the landslide constitutes the highest percentage among the other region at a rate of (63.94%) and an area (64.2 km²) of the total basin area of ​​(100.4 km²), while the least dangerous area occupies a percentage (33.67%) with an area of ​​(33.8 km²), and that Rate (2.39%) area (2.4 Km2) of the total area of ​​the aquarium exhibit to the possibility of severe danger of collapse.